2013
DOI: 10.1109/tasc.2012.2236138
|View full text |Cite
|
Sign up to set email alerts
|

Development and Test of a Single-Aperture 11 T $ \hbox{Nb}_{3}\hbox{Sn}$ Demonstrator Dipole for LHC Upgrades

Abstract: The upgrade of the LHC collimation system foresees installation of additional collimators around the LHC ring. The longitudinal space for the collimators could be provided by replacing some 8.33 T NbTi LHC main dipoles with shorter 11 T Nb 3 Sn dipoles compatible with the LHC lattice and main systems. To demonstrate this possibility, FNAL and CERN have started a joint program with the goal of building a 5.5 m long twin-aperture dipole prototype suitable for installation in the LHC. The first step of this progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 13 publications
1
66
0
Order By: Relevance
“…Parallel efforts are underway to establish complementary programmes in the United States, Japan, and other countries, in order to explore different SC-wire production lines and different coil layouts (e.g. cosθ coil [45], block coil [46], and canted cosθ coil [47] exceeded a field of 16 T at the coil [48]. While the FCC-hh design relies on Nb 3 Sn technology, the SPPC's 20 T accelerator dipole magnets must include a significant portion of high-temperature superconductor, for which both Bi-2212 or YBCO are being considered [13].…”
Section: Key Technologiesmentioning
confidence: 99%
“…Parallel efforts are underway to establish complementary programmes in the United States, Japan, and other countries, in order to explore different SC-wire production lines and different coil layouts (e.g. cosθ coil [45], block coil [46], and canted cosθ coil [47] exceeded a field of 16 T at the coil [48]. While the FCC-hh design relies on Nb 3 Sn technology, the SPPC's 20 T accelerator dipole magnets must include a significant portion of high-temperature superconductor, for which both Bi-2212 or YBCO are being considered [13].…”
Section: Key Technologiesmentioning
confidence: 99%
“…The design concepts of 11 T Nb 3 Sn dipole in single-aperture and twin-aperture configurations are described in [3,4]. The coil cross-section was optimized to provide a dipole field above 11 T in a 60 mm aperture at the 11.85 kA current with 20% margin, and geometrical field errors below 10 -4 .…”
Section: Magnet Design and Constructionmentioning
confidence: 99%
“…Therefore, the heater studies in MBHSP02 were performed at P AV =50-55 W/cm 2 . Simulations [12] and MBHSP01 heater studies [9] demonstrated that quench quite rapidly propagates in the radial direction from outer layer (OL) to inner layer (IL) coil blocks. Quench delay time was measured separatelly for OL and IL blocks both at 4.5 K and 1.9 K. To observe the quench propagation from the coil outer to the inner layer, the extraction dump was delayed by 1000 ms. Quench delay time was determined as the time between the heater ignition (t=0) and the voltage detection time in the coil (see Fig.…”
Section: B Protection Heater Studymentioning
confidence: 99%
See 2 more Smart Citations